Implication of Labour Turnover on Organizational Performance: A Case Study of Koboko Health Center IV - Juan Margret Ladu (Uganda Christian University, 2024)
This study looked into how employee turnover affects an organization's effectiveness as well as how these factors impact the medical care that staff members of Fort Portal Referral Hospital receive. The main worry shared by most organizations was that staff turnover is a costly process, particularly for those that prioritize the hospital's viability and prosper. Employee turnover is caused by a number of issues, including poor reward management, a lack of career advancement opportunities, a lack of health and safety, and ultimately a lack of desire. Determining the impact of employee turnover on organizational medical care delivery was the main goal of the research project. In order to gather quantitative and qualitative information that would clarify the characteristics of the impact of employee turnover on the provision of organizational medical services, the project used a descriptive research approach. The research study's target group consisted of all 70 workers who work at Koboko Health Center iv. In this study, stratified sampling was employed. Three categories were used to divide the target population: top management staff, medium level management staff, and junior staff. Structured questionnaires and oral interviews were used to gather primary data. Microsoft Excel was used to analyze the data that was gathered, and pie charts and tables were the results. Based on the study's findings, the organization needed to implement modern strategies to lower employee turnover rates because the rewards given to employees were insufficient, 61% of the workforce said that the company did not support their professional development, depriving them of a chance to advance in their careers, and 77% of the workforce said that low motivation contributed to the reality of higher employee turnover in the area of health and safety management. The study concluded with the following recommendations for the organization: to increase employee morale and motivation, the hospital should reevaluate its salary and benefit packages; to improve working conditions within the organization; to offer career growth opportunities; to involve employees in decision-making processes; and, finally, to implement strategies to lower employee turnover rates by keeping the best staff members in order to enhance organizational medical service delivery. The study came to the conclusion that poor management of incentives, career advancement, health and safety, and motivation had a detrimental impact on the organization's ability to provide medical services, which in turn affected the realization of higher staff turnover.